Graphene Oxide Reinforced Polylactic Acid/Polyurethane Antibacterial Composites. (11th September 2013) - An, Xiaoli; Ma, Haibin; Liu, Bin; Wang, Jizeng
Abstract : Nanocomposites from PLA/PU containing small concentrations of graphene oxide (GO) were prepared by simple liquid-phase mixing followed by casting. The as-prepared ternary PLA/PU/GO composite films exhibited good antibacterial activity against the gram-positive Staphylococcus aureus and the gram-negative Escherichia coli, due to the excellent antibacterial property of GO sheets with high specific surface area. The addition of GO inhibited the attachment and proliferation of microbes on the film surfaces, resulting in that the PLA/PU/GO composite films show remarkably improved antibacterial activity compared with PLA/PU composite film. The inhibition efficiency is proportional to the amount of GO. Furthermore, PLA/PU/GO composite fibrous paper was fabricated using electrospinning and exhibited good biocompatibility. The addition of GO does not destroy normal cell's proliferation and differentiation. PLA/PU/GO composites with good antibacterial activity and biocompatibility make it attractive for the environmental and clinical applications and also provide a candidate for future application of tissue engineering.